2014
DOI: 10.12691/ajidm-2-2-3
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Distribution of Human Onchocerciasis in Two Senatorial Districts in Ebonyi State, Nigeria

Abstract: Background: There has been a recent increase in the number of human Onchocerciasis cases in hospitals in Ebonyi Central. This study therefore sets out to determine the prevalence of the disease in Ebonyi North and Central Senatorial Zones of Ebonyi State as well as determine the age groups and sex most affected. Methods: This study was carried out in Ebonyi North and Central Senatorial Zones of Ebonyi State between January 2011 and April 2012, among subjects of 20-59 years. Diagnosis was by skin examination fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…A key limitation, of this study is the sole reliance on physical examination of symptoms by non-medical persons which may have lowered the precision of diagnosis. Future costing studies could combine physical examination and precise clinical methods, including biopsies and tests for visual acuity [ 36 ]. However, careful training and supervision of examiners used in this study may well have reduced this limitation to a barest minimum.…”
Section: Discussionmentioning
confidence: 99%
“…A key limitation, of this study is the sole reliance on physical examination of symptoms by non-medical persons which may have lowered the precision of diagnosis. Future costing studies could combine physical examination and precise clinical methods, including biopsies and tests for visual acuity [ 36 ]. However, careful training and supervision of examiners used in this study may well have reduced this limitation to a barest minimum.…”
Section: Discussionmentioning
confidence: 99%
“…In the preliminary stage, there is atrophy of germinal centers and sinus histiocytosis and, later, the replacement of lymphoid tissue by fibro-adipose tissue, which has a perivascular pattern in the later stages [113]. Lymphatic complications as a result of onchocerciasis are more distributed among the older population than the younger population [12,15,95,100,114] (see Table 2). Furthermore, some of the lymphatic complications predispose onchocerciasis elderly patients to other forms of lymphatic complications.…”
Section: Lymphatic Complications Due To Onchocerciasis In the Elderly Populationmentioning
confidence: 99%
“…On the other hand, some patients have an intact and symptomatic immune response to O. volvulus antigens [82]. Moreover, contrary to most phenotypes of OSL [14,15,95,114,121], pruritus has been reported to be more prevalent in the younger age group [12,15,100]. This may be due to the fact that the first visible symptom of onchocerciasis is OSLs, which usually begin with intense itching, followed by irritating papular rashes [122].…”
Section: Onchocercal Skin Lesions Among the Elderly Populationmentioning
confidence: 99%
“…36 Okoro et al also reported that the prevalence of blindness secondary to onchocerciasis was 28.5%. 37 A case series by Dozie et al reported six elderly patients with blindness secondary to onchocerciasis. 38 Most of the included studies in the literature included participants ≥50 years of age.…”
Section: Discussionmentioning
confidence: 99%